Hukum Pengangkatan Anak di Negara Muslim - Ravika Revira Ginting (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This paper examines the adoption (adoption) of children from the perspective of Islamic law in the world. This writing aims to find out how the law of adoption (adoption) of children in Muslim countries. This research uses library research by collecting qualitative data. This data was obtained from several sources such as books and journal articles. This study uses a normative approach by analyzing the rules that exist in several Muslim countries in the world, one of which is related to the law of adoption or adoption. The results of this study are that every Muslim country in the world has its own rules regarding adoption or adoption laws, especially those in Indonesia, Turkey, Malaysia, Jordan, Egypt and Tunisia.